Pengaruh Literasi Pajak, Modernisasi Sistem Perpajakan, dan Media Sosial terhadap Kepatuhan Wajib Pajak UMKM Kecamatan Serengan Kota Surakarta - Fernando Barlimanuana; Maya Widyana Dewi; Yuwita Ariessa Pravasanti (Jurnal Pajak dan Analisis Ekonomi Syariah, 2026)
This study aims to empirically examine the influence of tax literacy, tax system modernization, and social media on the tax compliance of Micro, Small, and Medium Enterprise (MSME) taxpayers in Serengan District, Surakarta City. The research population consisted of 2,189 MSMEs registered in Serengan District based on data obtained from the Surakarta City Cooperative and MSME Department. A sample of 73 MSMEs was selected using the purposive sampling technique according to predetermined research criteria. Primary data were collected through structured questionnaires distributed directly to MSME owners or managers. The collected data were analyzed using descriptive statistical analysis, validity and reliability tests, classical assumption tests, multiple linear regression analysis, hypothesis testing through the t-test and F-test, as well as the coefficient of determination (R²). The findings reveal that tax literacy does not significantly influence MSME taxpayer compliance. In contrast, tax system modernization and the utilization of social media have a significant positive influence on taxpayer compliance. These findings indicate that improvements in digital tax services and the effective use of social media as a communication and information platform can enhance voluntary tax compliance among MSME taxpayers.